DNA fingerprinting of five Tabebuia species with reference to their anti-trypanosomal activity - Seham El-Hawary; Rabab Mohammed; Marwa Taher; Sameh Fekry AbouZid; Sameh Fekry AbouZid; Elham Amin; Elham Amin (Faculty of Pharmacy, Mahidol University, 2022)
Tabebuia is the largest genus of the Bignoniaceae family, with great importance due to its beautiful decorative flowering trees, as well as, its remarkable biological activities. The exact identification of Tabebuia species is important, not only, for cultivation purposes but also for exploration of their phytochemical and biological potential. DNA fingerprinting technology is now considered an easily accessible, quick, and accurate method of species identification. The current study investigated the genetic diversity among five Tabebuia species, using start codon targeted (SCoT), and inter simple sequence repeats (ISSR) markers. Results indicated the efficiency of both markers for genetic fingerprinting of the five tested Tabebuia species with ISSR analysis being more polymorphic than SCoT analysis. The dendrogram generated from the combination of ISSR and SCoT analyses classified the tested species into two main clusters. Cluster I included T. guayacan, while Cluster II was separated into sub-cluster I comprising T. rosea and sub-cluster II that was further subdivided into sub-cluster IIa (T. pulcherrima) and sub-cluster IIb (T. argentea and T. pallida). Furthermore, the antitrypanosomal activity of the alcohol extracts of stems and leaves of the five tested Tabebuia was evaluated. Results revealed a variation in activity between extracts from different species. The highest antitrypanosomal activity was recorded for the stem and leaf extracts from T. pulcherrima, with IC50 (6.4-7.2 µg/mL) and (8.3 and 8.9 µg/mL) after 48 and 72 h respectively, followed by T. pallida leaf then T. rosea stem extracts.